Polymorphisms in equine immune response genes and their associations with infections - Horín, Petr; Smola, Jirrí; Matiasovic, Ján; Vyskocil, Mirko; Lukeszová, Ludmila; Tomanová, Katarína; Králík, Petr; Glasnák, Vladimír; Schröffelová, Dana; Knoll, Ales; Sedlinská, Markéta; Krenková, Leona; et al. (Mammalian genome, 2004)
Polymorphic markers identified in the horse genes encoding the interleukin 12 p40 subunit, interferon gamma, tumor necrosis factor receptor 1, and inducible nitric oxide synthase were identified and tested, along with additional markers, for associations with two important horse infections: Rhodococcus equi and Lawsonia intracellularis. Eight immune response-related and 14 microsatellite loci covering 12 out of 31 equine autosomes were used for the association analysis. Markers located on horse Chromosomes Eca10 and 15 were significantly associated with the presence of high numbers of R. equi in transtracheal aspirates. Significant associations of markers located on Eca9, 15, and 21 with fecal shedding of Lawsonia intracellularis were found. Marginal associations with tumor necrosis factor alpha, interferon gamma, and other genes suggested that variations in immune response-related genes could underlie the phenotypic variation observed.
Keywords: Lawsonia (bakterie); Nitric Oxide Synthase Type II; polymorfismus genetický; Rhodococcus equi; Horses; savčí chromozomy; interleukin-12; synthasa oxidu dusnatého; koně; zvířata; geny MHC třídy II; Polymorphism, Genetic; TNF-alfa; Lawsonia Bacteria; synthasa oxidu dusnatého, typ II; Genetic Predisposition to Disease; genetická predispozice k nemoci; Interleukin-12; Chromosomes, Mammalian; Genes, MHC Class II; interferon gama; Tumor Necrosis Factor-alpha; Animals; Nitric Oxide Synthase; Interferon-gamma